IMPLEMENTASI MANAJEMEN STRATEGIK DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMK NEGERI 6 SURAKARTA - Firzan Gifari; Wiedy Murtini; Cicilia Dyah (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2022)
The objectives of this research are for: (1) Implementation of Strategic Management in Improving the Quality of Education in SMK Negeri 6 Surakarta (2) Perceived barriers in the implementation of Strategic Management to improve the Quality of Education in SMK Negeri 6 Surakarta (3) Efforts made to overcome obstacles in the application of strategic management to improve the quality of education in SMK Negeri 6 Surakarta. This research is using a qualitative descriptive approach. The sources of data used in this research come from informants, places and events, as well as documents and archives.The sampling technique used is purposive and snowball sampling. The data collecting techniques used are interviews, observation ,and documentation. The data validity test is carried out by fulfilling the four principles of validity testing, namely Credibility, Transferability, Dependability and Confirmability. The data analysis used is an interactive analysis model with several processes, namely data collection, data reduction, data presentation and drawing conclusions.  The results showed that the implementation of strategic management at SMK Negeri 6 Surakarta has three stages, namely planning, implementation and evaluation. Barriers exist in supervision, human resources and student expectations. SMK Negeri 6 Surakarta overcomes these obstacles by conducting training, guidance and direction.